2005
DOI: 10.1063/1.2137450
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and field dependence of magnetoelectric interactions in layered ferromagnetic transition metal-piezoelectric lead zirconate titanate

Abstract: The strength of magnetoelectric (ME) coupling at 10Hz–3MHz has been measured in trilayers of Fe, Co, or Ni and lead zirconate titanate (PZT). The strongest ME coupling is measured for trilayers with Ni and the weakest in Co. Data on ME voltage coefficient αE versus bias magnetic field H for Fe–PZT–Fe show unique features including zero crossing and sign reversal. Measurements of frequency dependence of αE reveal a giant ME coupling due to the electromechanical resonance at 200–300kHz for radial modes and at ∼2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
37
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(44 citation statements)
references
References 12 publications
4
37
0
1
Order By: Relevance
“…It has been reported that ME output of Ni/PZT/Ni bulk ME sensor with 2-2 structure can have a value as high as 40-400 mV/cmÁOe. [22][23][24] The ME coefficient of our BiFeO 3 /Ni is much smaller than this value. It will be important to understand the limiting factors in order to maximize the ME output.…”
mentioning
confidence: 93%
“…It has been reported that ME output of Ni/PZT/Ni bulk ME sensor with 2-2 structure can have a value as high as 40-400 mV/cmÁOe. [22][23][24] The ME coefficient of our BiFeO 3 /Ni is much smaller than this value. It will be important to understand the limiting factors in order to maximize the ME output.…”
mentioning
confidence: 93%
“…[11][12][13][14][15][16][17]19,20 A resonance enhancement ͑ϳ100 times͒ of the ME voltage coefficient ͑V ME ͒ has been reported at the first longitudinal mode ͑f 0 ͒. [21][22][23] Such enhancement is potentially very important; however, it is limited to a relatively high frequency: for example, consider a 15 mm long Terfenol-D/PZT LT mode laminate, V ME Ϸ 18.5 V / cm Oe at f 0 Ϸ 80 kHz. 11 For ME laminates having a Terfenol-D layer͑s͒, a high resonant frequency of ജ10 kHz will result in significant eddy current losses due to the conductive nature of the Terfenol-D layer, which in turn will dramatically lower the efficiency of energy conversion.…”
mentioning
confidence: 99%
“…[11][12][13][14][15][16][17][18][19] In addition, most layered ME composite theoretical models stressed on the influence of thickness ratio of ferromagnetic and ferroelectric phases, but paid no attention on the influence of in-plane sizes on ME coefficient. [20][21][22][23] In fact, the magnetostrictivity is largely dependent on in-plane sizes due to shape demagnetization effect, so ME coefficients α E,31 and α E,32 would be different.…”
mentioning
confidence: 99%